Entrepreneurial behaviour of family firms : perspectives on emerging economies - Krasniqi, Besnik A.; Kraus, Sascha; Ramadani, Veland; Jones, Paul (Entrepreneurial behaviour series., 2024)
In emerging economies, one of the most prevalent types of business is the family firm, from small food carts to bigger nation-wide businesses and every type in between. Both internal factors such as family dynamic and culture, and external factors such as government policy and economic conditions can have varying impacts on the management and success of family firms. Offering perspectives on the entrepreneurial behaviour of family businesses in such economies, the chapters collected here present a systematic analysis focusing on gender, culture, policy, issues of succession, growth and economic impact. Contributors also discuss the positive impact of family business growth on local, regional and national economies, whilst examining challenges posed by the future in maintaining the family business. Researchers, policy makers and academics will benefit from this comprehensive picture of entrepreneurial behaviour of family business, providing major theoretical and empirical evidence and a brighter view of these fields from the perspective of emerging economies. The Entrepreneurial Behaviour series is dedicated to communicating innovative and multi-disciplinary new research that advances theory and practice in Entrepreneurial Behaviour. The series is focused on expanding the scope of Entrepreneurial Behaviour theory and analysis and enriching practice by encouraging multi-theoretical, multi-cultural and multi-disciplinary approaches.